Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.

Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. - Cortet, Jérôme; Poinsot-Balaguer, Nicole (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.
Keywords: Collembola; litter decomposition; Phenology; Quercus coccifera; Quercus ilex